Toward High‐Efficiency Solution‐Processed Planar Heterojunction Sb2S3 Solar Cells. Issue 5 (2nd April 2015) - Zimmermann, Eugen; Pfadler, Thomas; Kalb, Julian; Dorman, James A.; Sommer, Daniel; Hahn, Giso; Weickert, Jonas; Schmidt‐Mende, Lukas
<x xml:space="preserve">Abstract</x> Low‐cost hybrid solar cells have made tremendous steps forward during the past decade owing to the implementation of extremely thin inorganic coatings as absorber layers, typically in combination with organic hole transporters. Using only extremely thin films of these absorbers reduces the requirement of single crystalline high‐quality materials and paves the way for low‐cost solution processing compatible with roll‐to‐roll fabrication processes. To date, the most efficient absorber material, except for the recently introduced organic–inorganic lead halide perovskites, has been Sb2S3, which can be implemented in hybrid photovoltaics using a simple chemical bath deposition. Current high‐efficiency Sb2S3 devices utilize absorber coatings on nanostructured TiO2 electrodes in combination with polymeric hole transporters. This geometry has so far been the state of the art, even though flat junction devices would be conceptually simpler with the additional potential of higher open circuit voltages due to reduced charge carrier recombination. Besides, the role of the hole transporter is not completely clarified yet. In particular, additional photocurrent contribution from the polymers has not been directly shown, which points toward detrimental parasitic light absorption in the polymers. This study presents a fine‐tuned chemical bath deposition method that allows fabricating solution‐processed low‐cost flat junction Sb2S3 solar cells with the highest open circuit voltage reported so far for chemical bath devices and efficiencies exceeding 4%. Characterization of back‐illuminated solar cells in combination with transfer matrix‐based simulations further allows to address the issue of absorption losses in the hole transport material and outline a pathway toward more efficient future devices.